Newly designed CHS genic primers for four Zingiberaceae species (Alpinia mutica, Alpinia rafflesiana, Hornstedtia leonurus and Scaphochlamys kunstleri) - Akram, S.; Ab Ghani, N. I.; Khamis, S.; Zulkifly, S. (Institute of Physics Publishing, 2021)
Flavonoids are secondary metabolites. To date, 2000 naturally occurring flavonoids are known present in plants. These diverse groups of antioxidants are abundant in rhizomes and leaves of Zingiberaceae species. Flavonoids are expressed by many genes. The most studied is chalcone synthase (CHS) gene. However, no study has been performed to study CHS gene in four endemic and pharmacological known Zingiberaceae species: Alpinia mutica, Alpinia rafflesiana, Hornstedtia leonurus and Scaphochlamys kunstleri. Furthermore, A. rafflesiana and S. kunstleri are threatened species. Thus, this study aimed to develop new CHS primers for these selected species. A total of 43 sequences of CHS genes belong to Zingiberaceae and Costaceae were retrieved from the NCBI database. Then, BLASTN was used to check sequence similarities of the retrieved CHS sequences to these four studied species, other Zingiberaceae and Costaceae. In follow, all redundant sequences were excluded and 15 sequences were saved as the final dataset. These 15 sequences were used to design genic primers using Primer3 software and insilico analysed using OligoAnalyzer™ Tool. This study had successfully designed 12 new CHS genic primers. All the primers can be used for future studies to determine the presence and expression of CHS gene in these four species.